Efektivitas Massive Open Online Course (MOOC), Persiapan Kehidupan Berkeluarga Bagi Remaja - Phawestrina, Dessy (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Massive Open Online Course (MOOC) is a training method based on information and communication technology (ICT) that can accommodate training needs in the era of the industrial revolution 4.0 because it is large-scale, open, and can be accesed online by anyone and anywhere. This study aims to determine the effectiveness of the Massive Open Online Course of the Family Life Planning for Teenagers 2021 at the Representative of the National Population and Family Planning Agency of the Special Region of Yogyakarta. The research is qualitative descriptive with a combination of document study, observation and interview methods. The effectiveness of the training is known through evaluation using Kirkpatrick’s Four Level Evaluation Model. The results obtained are Participants giving a positive response to the training program, Facilitators and Organizers; Participants increased in knowledge, attitudes and skills; Participants showed changes in behavior between before and after training; and Participant’s behavior changes contribute to the organization. Thus it was concluded that overall the MOOC PKBR 2021 was declared effective, both in level 1 reaction, level 2 learning, level 3 behavior, and level 4 result